ERAP1 molecular characterization: Identification of a de novo allelic variant. (24th May 2018) - Padula, M. C.; Leccese, P.; Padula, A. A.; D'Angelo, S.; Martelli, G.
Abstract : The novel ERAP1 allelic variant is a missense polymorphism leading to the Arg53Pro substitution.